Est-il permis de tuer son père hérétique ou de le dénoncer à l’Inquisition ? L’évêque d’Orihuela et les fils de morisques - Isabelle Poutrin (Les Cahiers de Framespa)
In his treatise De Bello Sacro (1602), José Esteve, the bishop of Orihuela, adresses the following question: «Is it allowed to kill one’s heretical father or to denounce him to the Inquisition?» This article studies the corpus of authorities used by Esteve, showing that, during the 16th century, several influential authors close to the Inquisition firmly established the obligation, for the children of heretics, to denounce them to the Holy Office. Nevertheless, Esteve, facing the resistance of the moriscos of his diocese, resorts to the exegetic literature of the 15th century (Tostado’s commentary on the Deuteronomy) to find an alternative solution.